STUDENTS’ PERCEPTION OF TASK-BASED LEARNING IN ENGLISH CLASS IN XI GRADE AT SMA NEGERI 1 TEMBILAHAN HULU IN 2024/2025 ACADEMIC YEARS - Dini Qurrata Ayuni; Agus Mustajib; Maizarah (Program Studi Pendidikan Bahasa Inggris, 2025)
One of the methods in teaching English is Task-Based learning which means teaching method centered on students’ experiences and knowledge through tasks provided by the teacher. Understanding students’ perception enables teachers to adapt the strategy for more effective and efficient teaching, ensuring students feel included in the process. The purpose of this research is to find out to students' perception on the task-based learning in English class. The method used in this research is descriptive quantitative. To find out students’ perception, the researcher used the questionnaire consist of 31 statements and gathered the data from 33 students at SMA Negeri 1 Tembilahan Hulu. the results showed that there was a positive perception on the task-based learning in English class. 96.8, which falls within the “Agree” category according to the interpretation interval of 83 to 107. Moreover, it could be concluded that students perceived task-based learning as effective in meeting both personal and instructional needs, engaging students actively in learning, and supporting their development through clear instructions, social interaction, and meaningful tasks.